ANALISIS RASIO KEUANGAN DAN FINANCIAL DISTRESS SEBELUM DAN SESUDAH COVID-19 SUBSECTOR FOOD AND BEVERAGE - Putri, Dinda Ramadhani; Azis, Azolla Degita; Rizqi, Muhammad Nur (Politeknik Negeri Ambon, 2023)
after, and during the covid 19 pandemic. The sample taken was purposive sampling in food and beverage subsector manufacturing industry companies listed on the Indonesia Stock Exchange for the period 2018-2021. The data analysis method used is the difference test or the Anova analysis method. Where the results showed CR, ROA, DAR, and TATO there was a difference in financial distress every period of the year, except in 2021 CR there was no significant difference in FD. It is hoped that the results of this study can be a benchmark in determining policies to avoid financial distress.Keywords: financial distress, financial ratio, Altman z-score